2021
DOI: 10.1097/oi9.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Age and socioeconomic status affect access to telemedicine at an urban level 1 trauma center

Abstract: Objectives: Despite clinical and economic advantages, routine utilization of telemedicine remains uncommon. The purpose of this study was to examine potential disparities in access and utilization of telehealth services during the rapid transition to virtual clinic during the coronavirus pandemic. Design: Retrospective chart review. Setting: Outpatient visits (in-person, telephone, virtual—Doxy.me) over a 7-week period at a Level I Trauma Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…For example, a larger proportion of the VC required assistance with > 3 IADLs and had more cognitive impairment suggestive of the inability to independently drive to in-person programs, 23 yet virtual appointments remained accessible to these patients. Previously, age has been associated with decreased accessibility to virtual care 18 ; however, our findings reveal high-SES frail older adults are able to continue accessing FPP treatment following virtual assessments. This demonstrates the existing equity within the virtual FPP as a population both frail and elderly continued to access supportive care.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…For example, a larger proportion of the VC required assistance with > 3 IADLs and had more cognitive impairment suggestive of the inability to independently drive to in-person programs, 23 yet virtual appointments remained accessible to these patients. Previously, age has been associated with decreased accessibility to virtual care 18 ; however, our findings reveal high-SES frail older adults are able to continue accessing FPP treatment following virtual assessments. This demonstrates the existing equity within the virtual FPP as a population both frail and elderly continued to access supportive care.…”
Section: Discussioncontrasting
confidence: 57%
“…Markers of high SES have been found to improve older adults’ ability to access and navigate virtual care despite frailty. 18 One noticeable difference between the cohort demographics was a greater number of female participants. Females have a longer life expectancy than males, and high-SES females tend to seek care more often than males.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies are available all of them showing high patient and physician satisfaction, however not equal to face-to-face examination [ 21 , 50 52 ]. Especially older patients show lower acceptance rates [ 22 , 53 ]. Looking into a third-party perspective, Ariza-Vega et al [ 41 ] investigated 44 family caregivers who had an older family member with a previous hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pediatric surgical clinics have found that patients with public insurance or without insurance and non-white patients were more likely to miss telemedicine appointments [ 36 , 37 ]. In addition to socioeconomic differences, older age was found in some studies to be associated with lower telemedicine usage [ 38 , 39 ]. However, telemedicine may reduce barriers to care in certain complex and lengthy surgical evaluations, such as living kidney donors.…”
Section: Discussionmentioning
confidence: 99%